PERAN BRAND IMAGE DAN KUALITAS PRODUK DALAM MENINGKATKAN LOYALITAS PELANGGAN - Abdul Wakil (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2020)
Customers play an important role in a company. Various alternative and efforts must be made by the company to satisfy customer needs through various strategies that aim to make customers become loyal to the products produced by the company. The purpose of this study is to determine the effect of brand image on customer loyalty and the influence of product quality on customer loyalty. This study is categorized as a qualitative research sourced from existing theories and empirical research journals that are relevant to the variables examined in this study. The results of this study showed that brand image has a positive effect on customer loyalty, product quality has a positive effect on customer loyalty.